The Implementation of Debate Technique to Enhance the Students’ Speaking Skill - Michael Tianame; Bustami Usman; Asnawi Muslem (English Education Journal, 2019)
The objective of this research was to improve the quality of teaching and learning speaking by using debate technique at the tenth grade students of SMAN Modal Bangsa, Aceh. The academic year was 2017/2018. The participants of this research were 27 students at class X/IPA-5. The research was classroom action research which was done in two cycles.Eachcycle consisted of two meetings. There were two types of data namely quantitative data and qualitative data. The result of the first cycle shows that the percentage score for the researcher’s performance was 70 % which is categorized as good; while in the second cycle the score was 90 % which is categorized as very good. Regarding to the students’ involvement, the percentage score in the first cycle was 75% or in the middle category, and it increased significantly in the second cycle with the percentage 95% or in the excellent category.Furthermore, the class passing percentage in the pretest was 55,55 %, but it increased 81,48 %in the first cycle and 100 % in the second cycle.  It indicates that the success indicator is reached. Finally, the data from the questionnaire shows that the students responded positively to the use of debate technique in the process of teaching and learning speaking. The outcome of this research showed that using debate technique were able to improve the teacher’s performance in teaching speaking, and the students’ involvement in learning speaking. It also improved the students’ speaking skill. Key words:  Speaking Skill, Debate Technique, Classroom Action Research